The Military Garrisons of Henry IV and Henry V at Strata Florida, 1407 and 1415–16. (1st December 2015) - Riley, Jonathon
This article provides an analysis of the royal garrisons deployed at Strata Florida Abbey in late 1407 and in 1415, a subject largely ignored by previous studies. The garrison of 1407 was a punitive force during the closing stages of Glyndŵr's rebellion; that of 1415 was to suppress possible dissent during the absence of Henry V in the Agincourt campaign. The choice of Strata Florida is discussed, along with the size, cost, disposition and purveyance of the garrisons, in relation to the political sympathies of the Cistercian Order in Wales, the military geography and the available resources to sustain an armed body. The impact of the garrison on the religious community and on the surrounding area is assessed.